2022
DOI: 10.3390/ijerph19031765
|View full text |Cite
|
Sign up to set email alerts
|

Gaming Behaviors and the Association with Sleep Duration, Social Jetlag, and Difficulties Falling Asleep among Norwegian Adolescents

Abstract: The relationship between gaming and sleep is mostly informed by studies of addictive gaming behavior, thus limiting our understanding of sleep in the context of nonproblematic engaged gaming. The present study investigated whether addicted, problem, and engaged gaming behavior was associated with sleep duration, social jetlag, and difficulties falling asleep. The sample consisted of 13- and 16-year-old Norwegian adolescents (n = 3228) participating in the Health Behavior in School-Aged Children (HBSC) survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 74 publications
1
11
0
1
Order By: Relevance
“…Additionally, social jetlag is associated with high caffeine intake in teenagers (16) . In addition to poorer food choices, social jetlag is thought to increase sedentary behaviours as shown in our own small cross-sectional study, in which those with social jetlag had lower physical activity levels (17) , confirmed by Alves et al (18) Moreover, in addition to decreasing physical activity, an increase in other sedentary behaviours, such as gaming was observed (19) . When present on the long-term these negative lifestyle behaviours can cause a positive energy balance, which, when chronic, leads to an increase in waist circumference and BMI, and higher risk of obesity.…”
supporting
confidence: 61%
“…Additionally, social jetlag is associated with high caffeine intake in teenagers (16) . In addition to poorer food choices, social jetlag is thought to increase sedentary behaviours as shown in our own small cross-sectional study, in which those with social jetlag had lower physical activity levels (17) , confirmed by Alves et al (18) Moreover, in addition to decreasing physical activity, an increase in other sedentary behaviours, such as gaming was observed (19) . When present on the long-term these negative lifestyle behaviours can cause a positive energy balance, which, when chronic, leads to an increase in waist circumference and BMI, and higher risk of obesity.…”
supporting
confidence: 61%
“…In our analysis, the responses were categorised into two: ‘<5: poor life satisfaction’ and ‘≥5: good life satisfaction’. Various cross‐country and cultural analyses have used this scale to assess self‐rated life satisfaction 52–54 …”
Section: Methodsmentioning
confidence: 99%
“…Various cross-country and cultural analyses have used this scale to assess self-rated life satisfaction. [52][53][54] Physical activity was assessed with a single item adapted from the Physical Activity Screening Measure (PASM). 55 Adolescents answered: 'Over the past seven days, how many days were you physically active for at least 60 min/day?'…”
Section: Potential Explanatory Pathwaysmentioning
confidence: 99%
“…Research on the etiology and particular symptoms of digital addiction [ 6 , 7 ], by comparison with other behavioral addictions [ 3 ], is focused on sleep and mood disorders and recognizes that there are clear similarities in this regard between substance or behavioral addictions [ 3 ], including digital addiction [ 7 ]. A key symptom common to all forms of addiction is, indeed, sleep dysfunction [ 42 , 43 ].…”
Section: Digital Addiction: a New Problem Worldwidementioning
confidence: 99%
“…Sleep dysfunction does not happen in a void but results from complex interactions between internal (body and brain function) and external (environment) variables. These interactions need to be recognized and fully taken into account for approaching pathological sleep in digital addiction [ 27 , 35 , 43 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 ], as they have implications for preventive measures and clinical treatment.…”
Section: The Dopamine–serotonin Imbalance Hypothesismentioning
confidence: 99%